Progressionism Restorative Justice Policies in Achieving Rehabilitative Criminal Justice - Muhtar Hadi Wibowo; Ali Masyhar; Anis Widyawati (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
This study aims to deeply examine and analyze ideal restorative justice policies, focusing on actualizing rehabilitative criminal law enforcement. By directly observing law in action, it explores how these policies are implemented and their impact, providing insights into effective, humane approaches within the criminal justice system.The main problems are how are the progressivism of restorative justice policy works in actualizing criminal enforcement that is rehabilitative?. Research method is Socio Legal, which is done by studying secondary data and conducting interviews. After that, the collected data is analyzed through a qualitative way. The urgency of this study lies in the frequent use of restorative justice policies for prosecuting criminal offenders. Through comprehensive, recent socio-legal research, this study examines the ideal implementation of restorative justice to achieve rehabilitative criminal law enforcement. Findings indicate that restorative justice should enable law enforcers to use penal codes as rehabilitative tools. The study concludes that restorative justice policies should include compensation requirements proportionate to the perpetrator's crime, ensuring a balanced and effective rehabilitative approach within the legal framework.